Gestão da informação esportiva no contexto da inteligência competitiva em clubes de futebol: um estudo de caso no Marília Atlético Clube - Jorge, Carlos Francisco Bitencourt [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Information is an inherent component among all processes within an organization. In sports environment, there are several organizational processes which rely on information coming from different kinds of sports information sources, because from them, the decision-making information is made up, as well as the professional development. In sports environment, soccer, which is considered a national passion by the Brazilian society, stands out. Within soccer context, there are soccer clubs, institutions which are civil entities and the majority of them are unprofitable due to their structure and management model, whose central goal consists on promoting entertainment to population, and that automatically lifts up the passion by the referred sport. In the environment of football clubs is possible to observe a huge competitiveness. The club adopts effective management of information and work process of competitive intelligence (CI) can achieve competitive advantage against other clubs. From this perspective, the present research report aims at analyzing and making out the use of information in soccer clubs. In regard the methodological procedures, the ‘Study Case’ method has been picked out in order to be applied to Marília Atlético Clube (MAC), a sports club from Marília, upstate São Paulo, which answers the basic assumptions of the research purposes. Before the observations carried out in the Club, the management and uses of information from different hierarchy levels and sectors could be analyzed, as well as the form information is applied to obtain the competitive advantage. The research also emphasizes the importance of an information professional managing the management processes, both the IM and the CI. This way, it is intended to verify if the Club makes use of procedures regarding competitive intelligence, even if in an informal manner... (Complete abstract click electronic access below)

A informação é um componente intrínseco em todos os processos de uma organização. No ambiente esportivo encontramos várias fontes de informações e processos que se relacionam e geram informações que sob este contexto são classificadas como informação esportiva. Nesse ambiente esportivo encontramos o futebol, considerado pelo povo brasileiro como uma paixão nacional. No âmbito do contexto do futebol encontramos os clubes, entidades que em sua grande maioria devido a sua estrutura e modelo de gestão são entidades civis sem fins lucrativos, cujo objetivo central consiste em promover entretenimento para a população, o que automaticamente eleva a paixão pelo esporte em questão, o futebol. No ambiente dos clubes de futebol é possível observar uma enorme competitividade. O clube que adota uma gestão eficaz de informações e trabalha o processo de inteligência competitiva (IC). Sob este viés, a presente dissertação visa analisar e compreender o uso da informação em clubes de futebol de pequeno e médio porte do interior do estado de São Paulo. Desta forma, a pesquisa foi realizada no Marília Atlético Clube (MAC), Clube de futebol da Cidade de Marília, interior do estado de São Paulo, e que se enquadra nas características citadas. Para tanto, escolheu-se o método ‘Estudo de Caso’, cuja técnica aplicada foi a triangulação. A triangulação consiste na aplicação de três ou mais técnicas de coleta e análise de dados, visando obter uma visão ampliada da problemática que se está investigando. A aplicação de diferentes técnicas investigativas torna a pesquisa mais consistente, concedendo maior validade ao resultado obtido. Tais análises foram realizadas com o intuito de elaborar ações para a gestão de informação (GI), enfocando a IC no âmbito do MAC. Os resultados de pesquisa propiciaram identificar os tipos de informações existentes no Clube...
Keywords: Inteligência competitiva; Gerenciamento da informação; Gestão do conhecimento; Clubes de futebol - Administração